Sunflower planting date in southeastern Rio Grande do Sul. - Silveira, Expedito Paulo; Assis, Francisco Neto de; Gonçalves, Paulo Romeu; Alves, Gilmar Chaves (Pesquisa Agropecuaria Brasileira, 2014)
The availability of productive varieties, the use of oil for food and fuel purposes, and the utilization of protein meal as feedstuff source, respectively, promote the oilseed sunflower (Helianthus annuus L.) crop in southern Brazil; but certain factors limit yield. Apart from other agronomic problems, one limiting constraint is planting date. In order to study this, four sunflower varieties were seeded monthly from August to December, and from October to January, respectively in 1982 and 1983/84 seasons on Planossol (Albaqualf) soil at the Centro de Pesquisa Agropecuária de Terras Baixas de Clima Temperado (CPATB-EMBRAPA) Experiment Station, in Capão do Leão county (31ºC52’ S), RS, Brazil. Eight field trials and bench tests were performed to evaluate this practice on growth duration, seed and oil yields, and oil percentage. The early planting time (late winter and early spring) proportionates better grain yield and oil percentage in the grain, although the elongation of growth duration. This was attributed to favorable temperature and soil moisture incidence during blooming. Early planting promotes, additionaly, healthy crops and raw-material to oil industries in the off-season (from November to February).